Understanding Interaction Design and Student’s Engagement in Augmented Reality Card for Education - Kusumaningtyas, Ester Anggun (Universitas Ciputra, 2025)
Elementary students often get bored with passive teaching methods, such as listening to the teacher and paying attention to the blackboard, because they prefer playing the game, exploring things, and interacting with peers. Augmented Reality (AR) card games have emerged as an alternative education media, offering interactive 3D visuals that enrich the learning experience. This study explores how the interaction design of an AR card game influences the engagement of second-grade elementary school students in learning animal vocabulary. Using a qualitative case study approach, observation was conducted during one class session, and the collected data were analyze based on learning outcomes and interaction design principles. The findings revealed a dynamic engagement trajectory, with students starting with curiosity and excitement or needing AR guidance, then actively participating, becoming master, and finally becoming bored after repeated the AR card game. From student engagement, this study revealed that the AR interaction design of the card game fostered curiosity, motivation, enjoyment, collaboration, and attention. The study demonstrated that the 3D visualization, animation, gameplay, interaction variations, audio narrative, and text supported vocabulary development, contextual understanding, memory retention, and problem-solving. However, sustained engagement depends on the variety of AR interactivity, so the insights contribute to improve the user interaction and gameplay design.